Highly site-specific oxygenation of 1-methylhistidine and its analogue with a copper(II)/ascorbate-dependent redox system - Uchida, Koji; Kawakishi, Shunro (Biochimica et biophysica acta, 1990)
The reaction of histidine-related materials with copper(II) and ascorbate under physiological conditions has been studied chemically. We discovered that 1-methylimidazole and its analogues, including biological metaboliets l-1-methylhistidine and anserine (β-alanyl- l-methylhistidine), exhibited dramatic reactivity with copper(II)/ascorbate. Reaction of copper(II) and ascorbate occurs specifically at the C-2 position of the imidazole ring of l-1-methylhistidine and anserine derivatives with mono-oxygenation to give the 1-methyl-2-imidazolones in good to excellent yields (70–80%). The occurrence of an oxocopper(III) intermediate in the oxidation process of ascorbate is postulated.